Mapping the intersection of digitalization and social entrepreneurship: a systematic literature review using the TCCM framework - Satyam Pathak; Amandeep Kaur (Future Business Journal)
Abstract Social entrepreneurship focuses on finding solutions through sustainable and mission-driven activities to the issues of society. Recently, its intersection with digitalization has opened new avenues both in research and practice. However, there are limited studies on the topic in the form of systematic literature reviews. This paper aims to review the literature to investigate the intersection of digitalization and social entrepreneurship. In-depth insights from the review of 73 papers selected from the Scopus database, following a structured methodology comprising the PRISMA guidelines, were reported using the theory, context, characteristics, and methodology (TCCM) framework. Using the TCCM review framework, this research gives an overview of dominant theories, contexts (i.e., sectors and countries), characteristics (i.e., digital capabilities, stakeholder engagement, organizational resilience and legitimacy, economic sustainability, purpose-driven service delivery, entrepreneurial intention and behavior) and research methods applied in the literature on the topic. Insights from the literature have been summarized in this paper, and a comprehensive framework is proposed to understand the topic. Future research directions are also suggested in the paper based on the TCCM framework, along with practical implications and challenges.